Alternative splice variants of DCLK1 mark cancer stem cells, promote self‐renewal and drug‐resistance, and can be targeted to inhibit tumorigenesis in kidney cancer. Issue 5 (16th April 2018) - Ge, Yang; Weygant, Nathaniel; Qu, Dongfeng; May, Randal; Berry, William L.; Yao, Jiannan; Chandrakesan, Parthasarathy; Zheng, Wei; Zhao, Lichao; Zhao, Karena L.; Drake, Michael; Vega, Kenneth J.; et al.
Abstract : Renal cell carcinoma (RCC) is a common and devastating disease characterized by a hypoxic microenvironment, epithelial‐mesenchymal transition and potent resistance to therapy evidencing the presence of cancer stem cells (CSCs). Various CSC markers have been studied in RCC, but overall there is limited data on their role and most markers studied have been relatively nonspecific. Doublecortin‐like kinase 1 (DCLK1) is a validated CSC marker in the gastrointestinal tract and evidence for an equivalent role in other cancers is accumulating. We used bioinformatics, immunohistochemistry, flow cytometry, spheroid self‐renewal and chemoresistance assays in combination with overexpression and siRNA‐knockdown to study the stem cell‐supportive role of DCLK1 alternative splice variants (DCLK1 ASVs) in RCC. To target tumor cells expressing DCLK1 ASVs directly, we developed a novel monoclonal antibody (CBT‐15) and delivered it systemically to RCC tumor xenografts. DCLK1 ASVs were overexpressed, enriched together with CSC markers and predictive of overall and recurrence‐free survival in RCC patients. In vitro, DCLK1 ASVs were able to directly stimulate essential molecular and functional characteristics of renal CSCs including expression of aldehyde dehydrogenase, self‐renewal and resistance to FDA‐approved receptor tyrosine kinase and mTOR inhibitors, while targeted downregulation of DCLK1 reversed these characteristics. Finally, targeting DCLK1 ASV‐positive cells with the novel CBT‐15 monoclonal antibody blocked RCC tumorigenesis in vivo . These findings establish DCLK1 as a CSC marker with implications for therapy, disease progression and survival in RCC and demonstrate the therapeutic value of DCLK1‐targeted monoclonal antibodies against renal CSCs. Abstract : What's new? Doublecortin‐like kinase 1 (DCLK1) is a validated marker for cancer stem cells in the gastrointestinal tract but its role in other cancers is unclear. Here, the authors demonstrate that specific DCLK1 alternative splice variants are overexpressed in renal cell cancer and drive self‐renewal and resistance to standard of care chemotherapies in cell culture coexpression experiments. As targeting the extracellular domain of DCLK1 variants by a monoclonal antibody (CBT‐15) results in strong inhibition of tumor growth in vivo, these findings may open new therapeutic options for patients afflicted with this commonly intractable cancer.